Electrical Muscle Stimulation Device - salim, Zubaida omar; salim, Sabaa omar; Qasim, Adham Qais (American Journal of Botany and Bioengineering, 2024)
The mind is the one that issues orders (nervous signals) to the main muscles to carry out the movement and at the same time gives instructions to other muscles to do the work of assistance and stabilization. Conversely, some muscles work in opposition to the main muscles to protect the individual from the force of contraction of the main muscles and thus the occurrence of injury. Which has spread recently in a striking manner, especially back injuries due to lack of movement and inactivity. As a result of technological progress and scientific development, many means and devices have been introduced in order to speed up the rehabilitation and treatment of injuries. Electrical stimulation has had a major role in the rehabilitation of some injuries. Its idea is to introduce electrical current to the muscles so that they work apart from the nerve signals issued by the brain through the spinal cord to the motor nerves to produce movement, and this What we clearly notice when an individual is exposed to electrical contact is that the muscles work involuntarily, and that the use of stimulation maintains the functional efficiency of the muscle and nerve, in addition to working to disrupt the pain signals emanating from the brain by creating an alternative sensory mechanism.